Student Engagement In Civic Learning: A Study For Practice - Patmisari; Setyawati, Sri; Muthali’in, Achmad; Prasetiyo, Wibowo Heru (Universitas Nusantara PGRI Kediri, 2021)
The problem that challenges the educators is increasing the engagement of students as young citizens in learning activities. In the context of civics learning, student engagement in the classroom can be the first and important indication that illustrates their future likelihood of becoming active citizens and responsible for managing common issues. More than that, learning engagement becomes a pretension for the level of learning participation as well as optimization of the student-centered approach. This study was conducted qualitatively in a school on civic education learning. The informants involved consisted of teachers and students using interview, observation, and document techniques. The focus of the study is directed at disclosing forms of student involvement in civic learning, teacher constraints in increasing student engagement, and efforts to overcome some of the existing obstacles. The results showed that the form of student engagement was shown by actively working on the questions given by the teacher, appearing in front of the class, expressing opinions, responding to the opinions of other students. The obstacle found was that not all students' abilities were the same in participating. The solution given in this research is good classroom management. Keyword: youth citizen, student engagement, civic education